Start-Up size and Post-Entry Performance: The Case of Tourism Services in Italy - Enrico Santarelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1996)
In this paper a large and comprehensive longitudinal data base is used to identify the start-up of new firms in Italian tourism services and their subsequent post-entry performance. Ana lysed in particular is the link between the survival and growth of hotels, restaurants, and catering firms in each Italian region and their start-up size. While it was found that in twelve out of twenty regions the likelihood of survival is significantly influenced by the start-up size, Gibrat's Law proved to hold for most regions, in contrast to the results found by several authors with regard to other sectors and countries. This implies that whereas larger newborn firms in the tourism sector have in most Italian regions a higher probability of survival than their smaller counterparts, the probability of a proportionate change in size during the relevant period is the same for all firms belonging to this sector in the large majority of regions.
Keywords: 330